Perancangan Sistem Informasi Pelayanan Reservasi Meja pada Metro Billiard - Nurafifah Salwa Alfian, Putri; Primadani, Joshua; Bintang, Fabio; Nur Wahida Putri, Ahda (SURYA TEKNIKA, 2025)
Metro Billiard is a recreational facility that provides billiard services for customers in Balikpapan. To support operational activities, service accuracy, and customer convenience, this study developed an information system using the Rapid Application Development (RAD) approach. RAD was selected for its ability to accelerate system development through iterative processes and active user involvement. The resulting system features real-time table availability, online reservation, waiting list management, and digital payment options, all designed to enhance efficiency and service transparency. Evaluation results show that the system successfully integrates key service functions, reduces administrative errors, and speeds up operational processes. This implementation provides significant benefits for Metro Billiard by improving service quality, modernizing operations, and increasing competitiveness in the digital era.